The Influence of the Construction of the Trans Sumatra Toll Road Binjai – Pangkalan Brandan Section on the Development of the Langkat Regency Area - Edwart Haloho; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
This study aims to examine the Influence of the Construction of the Trans Sumatra Toll Road Binjai – Pangkalan Brandan Section on the Development of Langkat Regency. This research method uses a qualitative method. The data analysis that will be carried out consists of description and analysis, the content of the description of the researcher will present the data or research results through the data collection techniques above. This method aims to describe a state or phenomenon. The results of the research Toll road construction is more enjoyed by areas that are the destination of movement, while areas that are not the destination of movement tend to be less advantageous. In areas that are the destination of movement, economic activity and economic growth tend to continue to increase, while in areas that are not the destination of economic activity and economic growth tend to decrease. The construction of toll roads in Langkat Regency provides more macroeconomic benefits and the construction of toll roads is development for the common good and welfare of the community in order to provide wider benefits so that the development is urgently needed. The construction of the Trans Sumatra Toll Road provides a change in land use that results in a change in community patterns, resulting in changes in community patterns. The development of the area after the operation of the toll road still has opportunities to continue to be developed.